THE CORRELATION PERFORMANCE OF THE EXTENSION AGENT WITH THE LIVELIHOODS AND MEMBERS MINDSET OF SYARIAH FISH FARMER GROUP IN SUNGAI BERINGIN TOWN, LIMA PULUH KOTA DISTRICT, WEST SUMATRA PROVINCE - Firma Pertiwi; Zulkarnain Zulkarnain; Kusai Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT The study on the correlation performance of the extension agent  and Livelihoods and Mindset was carried out in March 2018 in Sungai Beringin Town, Lima Puluh Kota District, West Sumatra Province. The study aims to determine  Performance of the extension agent in Syariah fish farmer group, advance understanding  livelihoods and mindset of the Syariah fish farmer group members, and knowing the correlation between performance of the extension agent with livelihoods and mindset of the Syariah fish farmer group members. The method used in this study is survey method which was analyzed using descriptive analysis and Vectorial Project Analysis (VPA) and the number of respondents in this study were 24 respondents.The results of the study analysis, performance of the extension agent in Syariah fish farmer group obtained a score of 1599 and were in the good category. Based on the analysis of VPA (Vectorial Project Analysis), there is a change in livelihoods and mindset of the Syariah fish farmer group from the preparation stage to the growth stage, which is up from 4.51 to 5.19. The relationship between the performance of extension agent and the livelihoods and mindset of Syariah fish farmer group members is that the agent influences the knowledge and awareness of the members in participating in counseling, adopting technology and information obtained from extension activities so that the mindset of group members increases towards a better one.Keywords: correlation, performance of the extension agent , livelihood and mindset